Pregunta
upstudy study bank question image url

\( 2.2 e^{x}-(3+e)=-3 e^{1-x} \) 3 Find the first four terms in the Binomial expansion of \( \frac{1}{\left(\frac{1}{\ln e}+e^{\ln (-3 x)}\right)^{2}} \)

Ask by Guerrero Ortega. in South Africa
Feb 24,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The first four terms in the Binomial expansion are \(1 + 6x + 27x² + 108x³\).

Solución

We wish to expand   1   ————————————   [1/ln(e) + e^(ln(–3x)]² step‐by‐step. Step 1. Simplify the expression under the square. Notice that ln(e) = 1 so that   1/ln(e) = 1. Also, e^(ln(–3x)) = –3x (provided –3x is within the domain of the logarithm). Thus, the expression becomes   1/[(1 – 3x)²]  or  (1 – 3x)^(–2). Step 2. Find the Binomial expansion of (1 – 3x)^(–2). Recall the general binomial expansion for a power –k:   (1 + t)^(–k) = Σ [n=0 to ∞] (n+k–1 choose n)·(t)ⁿ for |t| < 1. Here, we set k = 2 and let t = –3x. However, it is actually simpler to use the well‐known expansion:   (1 – u)^(–2) = Σ [n=0 to ∞] (n + 1) uⁿ    (for |u| < 1). In our problem u = 3x (note that the original expression is (1 – 3x); the minus sign is already “built in” to the binomial form). Thus,   (1 – 3x)^(–2) = Σ [n=0 to ∞] (n + 1) (3x)ⁿ. Step 3. Write the first four terms of the expansion. For n = 0:  Term₀ = (0 + 1)·(3x)⁰ = 1 For n = 1:  Term₁ = (1 + 1)·(3x)¹ = 2·3x = 6x For n = 2:  Term₂ = (2 + 1)·(3x)² = 3·9x² = 27x² For n = 3:  Term₃ = (3 + 1)·(3x)³ = 4·27x³ = 108x³ Step 4. Write your final answer. The first four terms in the expansion of   1/[(1/ln e + e^(ln(–3x))]² are   1 + 6x + 27x² + 108x³. Remember, this expansion is valid for |3x| < 1, i.e. |x| < 1/3.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Mind Expander

To solve the equation \( 2.2 e^{x}-(3+e)=-3 e^{1-x} \), we first rearrange it to isolate terms involving \( e^x \). This simplifies to \( 2.2 e^{x} + 3 e^{1-x} = 3 + e \). Next, we can substitute \( e^{1-x} = \frac{e}{e^x} \) to make it easier to work with. Once we find \( x \), we can use that in the second part. Now, for the binomial expansion of \( \frac{1}{\left(\frac{1}{\ln e} + e^{\ln (-3x)}\right)^{2}} \), note that \( e^{\ln (-3x)} = -3x \) using the property of logarithms. So we essentially want to expand \( \frac{1}{\left(1 + (-3x)\right)^{2}} \). Utilizing the binomial series, we can write: \[ \frac{1}{(1 - 3x)^{2}} = \sum_{n=0}^{\infty} \binom{n+1}{1} (3x)^n \] The first four terms would be: 1. \( \binom{1}{1}(3x)^0 = 1 \) 2. \( \binom{2}{1}(3x)^1 = 6x \) 3. \( \binom{3}{1}(3x)^2 = 27x^2 \) 4. \( \binom{4}{1}(3x)^3 = 108x^3 \) Thus, the first four terms are \( 1 + 6x + 27x^2 + 108x^3 \).

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad